Electrical and optical characteristics of SnO2 thin films prepared by dip coating from aqueous colloidal suspensions - Souza, A. E. de [UNESP]; Monteiro, S. H.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Springer Nature, 1997)
Starting from aqueous colloidal suspensions, undoped and Nb5+ doped SnO2 thin films have been prepared by using the dip-coating sol gel process. X-ray diffraction results show that films are polycrystalline with crystallites of average size1-4nm. Decreasing the thickness of the films and increasing the Nb5+ concentration limits the crystallite size growth during firing. Complex impedance measurements reveal capacitive and resistive effects between adjacent crystallites or grains, characteristic of electrical potential barriers. The transfer of charge throughout these barriers determines the macroscopic electrical resistance of the layer. The analysis of the optical absorption spectra shows that the samples present more than 80% of their transmittance in the visible region and the value of the band gap energy increases with decreasing crystallite size. © 1997 Chapman & Hall.
Keywords: Coating techniques; Crystal growth; Crystal structure; Electric impedance measurement; Electric properties; Electric resistance; Energy gap; Film preparation; Optical properties; Semiconducting films; Sol-gels; X ray diffraction analysis; Aqueous colloidal suspensions; Band gap energy; Complex impedance measurements; Dip coating; Tin dioxide; Semiconducting tin compounds